Cannabis and Driving - Pearlson, Godfrey D.; Stevens, Michael C.; D'Souza, Deepak Cyril (Frontiers in Psychiatry, 2021)
As more states in the U.S legalize recreational and medicinal cannabis, rates of driving under the influence of this drug are increasing significantly. Aspects of this emerging public health issue potentially pit science against public policy. Issues such as detection of cannabis-impaired drivers, use of blood THC levels to gauge impairment, and use of simulated driving to gather data should rely heavily on current scientific knowledge. In this article we review various sorts of current information linking cannabis to motor vehicle accidents and carefully review patterns of cannabis-impairment of driving related behaviors, their time courses, relationship to cannabis dose and THC blood levels, and compare cannabis and alcohol-impaired driving patterns directly. This review also delves into questions of alcohol-cannabis combinations and addresses the use of per-se limits in cannabis driving convictions. Finally, we distinguish between areas where research has provided clear answers to the above questions, areas that remain unclear, and make recommendations to fill gaps in current knowledge.